Inoculant and urea-molasses additives for forage sorghum silage - Hinds, M.; Brethour, J.; Bolsen, K.; Ilg, H. (Kansas State University. Agricultural Experiment Station, 2011)
An inoculant (Sila-bac) and a non-protein nitrogen (LSA-100) silage additive were evaluated with whole-plant, forage sorghum silage. Sila-bac silage had the fastest temperature rise and peaked at 10 C above its initial temperature. LSA-100 silage had a slow, steady temperature rise and reached a maximum of 22 C above its initial. Control silage peaked at 15 C above its initial. Steers fed LSA-100 silage gained 7 to 9% faster than did those fed control or Sila-bac silages. LSA-100 silage was consumed in greatest amount; Sila-bac silage, in the least. The two additives improved feed efficiency by 3% over the control. Both additives improved aerobic stability; control silage heated after 3 days; Sila-bac and LSA-100 after 7. Dry matter recovery from the stave silos was similar for control (78.1%) and LSA-100 silages (77.3%), but higher for Sila-bac silage (81.2%). When fermentation, storage, and feedout losses were combined with steer performance, pounds of gain per ton of ensiled forage were 88.8 for Sila-bac, 84.5 for LSA-100, and 82.6 for control silages.
Keywords: Beef; Sorghum silage; Feed efficiency; Aerobic stability; Dry matter